1996_05 Insight May 1996 - Dept. of Journalism, California State University, Fresno (Publisher):::::::::
Weekly during the school year. Vol. 1, no. 1 (Oct. 8 1969-v. 29, no. 23 (May 13, 1998, issue. Title from masthead. Merged with Daily collegian.